TEORI AKUNTANSI: DARI PENDEKATAN NORMATIF KE POSITIF - ARIF BUDIARTO; MURTANTO MURTANTO (Jurnal Bisnis dan Akuntansi, 1999)
Recent attention in accounting has focused on developing a positive theory which a major force in academic accounting research for almost two decades. The philosophical objective of positive accounting theory is to explain and predict current accounting practice. Positive theory, seeks to understand why accounting practices are employed by accountantsin different circumtances and by different firms. In contrast, normativetheory have often argued for a change in accounting method withoutputting forward any supporting empirical evidence and without tryingto understand the rationale for the status quo. One criticism of normativeaccounting theory is that it makes certain prescriptions for accountingand auditing practice which are not based on identified and empiricalobservations. An appreciation of difference between positive and normative accounting theories is necessary for any understanding of accounting theory. This is especially so because positive accounting theory has been a strongly supported paradigm in accounting research during the past decade, but the relative importance of positivism and normativism in accounting has been keenly debated for at least 25 years.